1993
DOI: 10.1159/000111321
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Myelinogenesis Induced by Dietary Lipids in Rats

Abstract: Our previous work has shown an early development of behavioral reflexes in the offspring of rats maintained on diets containing a lipid fraction extracted from yeast (Candida lypolitica) grown on n-alkanes during pregnancy and throughout lactation. Since some of these changes could be linked to an early myelination, in this study we investigated myelin maturation in the rat brain by immunohistochemistry. At 7 days the test groups showed considerable immunopositivity to myelin basic protein and proteolipid prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Diet in particular has been studied in the context of developmental myelination, where polyunsaturated fatty acids (PUFAs) have been linked to increased myelin gene expression and protection against white matter injury, with PUFA administration during maternal gestation leading to accelerated myelination and early development of behavioral reflexes (Confaloni et al, 1993;Gozzo et al, 1982;Salvati et al, 1996;Salvati et al, 2002;Tian et al, 2011;Tuzun et al, 2012). PUFAs are integral components of cell membranes including myelin membranes (Yurlova et al, 2011).…”
Section: Common Effectors? the Potential For Intersecting Mechanisms mentioning
confidence: 99%
“…Diet in particular has been studied in the context of developmental myelination, where polyunsaturated fatty acids (PUFAs) have been linked to increased myelin gene expression and protection against white matter injury, with PUFA administration during maternal gestation leading to accelerated myelination and early development of behavioral reflexes (Confaloni et al, 1993;Gozzo et al, 1982;Salvati et al, 1996;Salvati et al, 2002;Tian et al, 2011;Tuzun et al, 2012). PUFAs are integral components of cell membranes including myelin membranes (Yurlova et al, 2011).…”
Section: Common Effectors? the Potential For Intersecting Mechanisms mentioning
confidence: 99%
“…The type of lipid fed is also associated with morphological and biochemical changes in myelin subfractions of developing rats [Salvati et al, 1984;Srinivasaro et al, 1997], and fat intake influences the developmental increase in the mRNA levels for proteolipid protein, myelin basic protein and stearoyl CoA desaturase in the brains of neonatal mice [DeWille and Farmer, 1992]. Confaloni et al [1993] suggest that dietary lipids or their metabolites play a direct role in transducing intra-or extracellular signals, triggering cellular events that regulate the differentiation, proliferation and migration of oligodendrocytes, from which myelin is derived.…”
mentioning
confidence: 99%
“…By 21 days, the levels of myehin proteins were present in the test group at control levels. Further results (Confaloni et al, 1993) have shown that at 7 postnatal days in rats fed microbial lipid, MBP-and PLP-positive fibers are already present in a more rostral level such as the corpus callosum. In controls, the staining fibers were detected later in brain development.…”
Section: Fig 3 Distribution Of Oligodendrocytesmentioning
confidence: 87%